Therapeutic potential of medicinal plants for the management of renal stones: A review - Mohammed I. Rasool; Tariq H. Mousa; Hayjaa M. Alhamadani; Ahmed H. Ismael (Baghdad Journal of Biochemistry and Applied Biological Sciences)
Kidney stone disease is the third most common urological ailment worldwide, people. The mechanism of stone formation includes: urine supersaturation, aggregation, retention, nucleation, and growth of crystals in the cells of the renal tubular epithelium. Kidney stones may cause extreme pain and blockage of urine flow. They are usually treated with conventional drugs and shock wave (ESWL) as well as a variety of medications that may cause several adverse effects. The remaining stone fragments and the risk of infection following ESWL are major challenges in the treatment of kidney stones. Recently, despite the emergence of modern drugs, medicinal plants have been recognized and utilized in many nations clinically due to their safety profile, efficiency, cultural acceptance, and fewer side effects than approved drugs. Medicinal plants are used in different cultures as a reliable source of natural remedies. The aim of this review is to provide comprehensive information about traditionally used plants as well as their scientifically proven pharmacological activities, their primary chemical ingredients, and potential mechanisms of action, such as analgesic, astringent, demulcent, diuretic activity, antioxidant activity, inhibition of the inflammatory process, nucleation inhibition, crystallization inhibition, inhibition of crystal aggregation, reducing , reducing stone size, and reducing urine supersaturation.